(untitled) (The International Journal for Scientific Research, 2023)
The study aimed to find out the extent to which Saudi women depend on the Twitter platform in developing their health awareness and to stand up to Saudi women’s evaluation of the role of the Twitter platform in developing their health awareness. The population of the Kingdom of Saudi Arabia is women in Al-Ahsa Governorate who are exposed to health contents via the Twitter platform, with a size of 200 items, relying on the questionnaire as a tool for this study. Cognitively as a result of her reliance on the Twitter platform in the field of health awareness, more than emotional and behavioral vulnerability, and there is a strong direct relationship between the rate of Saudi women’s reliance on the Twitter platform in health awareness and the level of benefit achieved from this reliance.